Complete mitochondrial genome of Teratoscincus przewalskii (Reptilia, Squamata, Sphaerodactylidae) and phylogenetic analysis. Issue 11 (2nd November 2021) - Yu, Hui; Liu, Yang; Liu, Yan; Yang, Junmei; Li, Siqi; Bi, Junhuai; Zhang, Ruidong
Abstract: The complete mitochondrial genome of the lizard, Teratoscincus przewalskii, which belongs to the family Sphaerodactylidae was determined based on Illumina data in this study. The result showed that the closed double-stranded circular mitogenome was 16, 779 bp in total length (GenBank accession number: MW491837) with 44.07% GC. The complete mitochondrial genome consisted of 13 protein-coding genes, 22 transfer RNA genes, two ribosomal genes, and one noncoding control region. Phylogenetic analysis using mitochondrial genomes suggested that T. przewalskii was most closely related to its congener T. keyserlingii . This work provides valuable molecular information for further research on species identification and molecular evolution.